Thermal and computational fluid dynamics analysis of an oil fired crucible furnace during secondary aluminum smelting - Biodun Owolabi, Oluwasegun; Opeyemi Osoba, Lawrence; Oluropo Adeosun, Samson (Journal of Production Engineering, 2020)
Thermal and computational fluid dynamics (CFD) analyses were explored using knowledge-based software, including SolidWorks and ANSYS Workbench 14.0, to model and simulate an oil-fired crucible furnace utilized in the secondary smelting of aluminum. The thermal analysis revealed maximum heat flux and directional heat flux values of 8.7596 W/mm² and 8.0349 W/mm², respectively. Additionally, CFD simulations indicated that the influence of process parameters on the furnace components stemmed from various furnace-related factors. In summary, theoretical calculations of thermal stress within the furnace and heat transfer to the crucible align with the results obtained through modeling and simulation.